STUDI PENGEMBANGAN PERANGKAT PEMBELAJARAN (BAHAN AJAR) DI MTS AL-KHAIRAT KOTA TERNATE - Dahlan Usia; Jainudin Abdullah (Jurnal Geocivic, 2018)
The development of learning devices and teaching materials is essentially the development of short-term learning tools to estimate or project what will be done in learning activities. The development of learning tools and teaching materials are translated from syllabus or RPP to direct students' learning activities in an effort to achieve Basic Competency. This research is descriptive qualitative researchers with data collection techniques, namely: (1). Observation Technique; (2). Interview technique; and (3). Documentation techniques. As for the purpose of this study to find out the development of learning devices and teaching materials at MTs Al-Khairat.  Kota Ternate and to find out the factors that influence the development of learning devices and teaching materials. The results of this study indicate that the development of learning devices and teaching materials at MTs Al-Khairat. Kota Ternate are as follows: (1). learning devices and teaching materials at MTs Al-Khairat Kota Ternate in using educational unit level curriculum. But in the study of compost and its substance there are some teachers who have not understood substantially. Without formulation and indicators that have been set in the development of learning devices; and (2) In the development of learning devices and teaching materials at MTs Al-Khairat.  Kota Ternate begins with an analysis of subject matter in accordance with standards and compotency expected in the formulation of the development of learning tools namely (RPP) and syllabus, where teachers are still experiencing difficulties. This is due to the lack of involvement of teachers in developing their competence or training in developing teaching materials / learning devices. Keywords: Development, Teaching Materials, MTs Al-Khairat  Kota Ternate